EFEKTIVITAS PERBANDINGAN MODEL PEMBELAJARAN SYNECTIC DENGAN MODEL KONVENSIONAL (CERAMAH) TERHADAP KEMAMPUAN BERPIKIR KREATIF SISWA - Nur Alia; Thamrin Tayeb; Rafiqah Rafiqah (Jurnal Biotek, 2016)
The study discusses the comparative of the effectiveness of synectic conventional learning model on the creative thinking abilities of students with the aim to determine (1) the ability of creative thinking of students who were taught using conventional learning models (lectures) in VII grade SMP Negeri 3 Pattallassang, ( 2) the ability of creative thinking of students taught using Synectic learning model in VII grade SMP Negeri 3 Pattallassang, (3) the comparative of the effectiveness of the Synectic learning model effective towards creative thinking abilities in VII grade SMP Negeri 3 Pattallassang.The study is a Quasi-Experimental Research Design with non-equivalent control group design. The study population is all students of VII grade SMP Negeri 3 Pattallassang as much as  98 students consisting of VII1 class to VII3 class. The sample in this study is VII1 class as a control class while VII3 class as an experiment class. Instruments used in this research is students creative thinking test, such as pretest and posttest and observation sheet. Data analysis technique is descriptive statistical analysis and inferential statistical analysis.Based on the analysis using descriptive statistics in the experimental class, pretest score mean is 5.9 and the posttest score mean is 11.63 whereas the control class, the score mean is 6.1 for pretest and 9.16 for posttest. Based on effectiveness  test result to determine effectiveness of the learning model Synecti. Thus, the value of R <1, namely 0.89 <1, which means relatively θ1 more efficient than θ2. It means that there is a difference posttest score variance of experimental class and posttest score variance of control class. Hence, Synectic learning model is effectively used towards creative thinking abilities of students of VII grade SMP Negeri 3 Pattallassang Gowa.